Estimation of erosion resistance of hardened metal alloys under conditions of droplet impact - O. V. Kudryakov; V. N. Varavka; I. Yu. Zabiyaka; N. I. Bronnikova (Advanced Engineering Research)
Introduction. The phenomenon of the droplet impingement erosion which develops in the metallic materials at the frequencies of drop collisions of 50 ... 200 s-1 and velocities of 150 ... 600 m/s is considered. The comparative estimability of the wear resistance of materials of various structural classes and with different levels of mechanical properties is investigated. The major goal of the work is the development of a computational and analytical model of erosion wear of hardened materials. In parallel, the problem of the criterial evaluation of materials, with the help of which they could be attributed to plastic or reinforced materials and then used as a corresponding model of the fatigue failure mechanics, is solved.Materials and Methods. The well-known dependences of the fracture mechanics and the fatigue theory of Paris-Erdogan are used for the computational and analytical estimates of the erosion resistance of materials. The calculated expressions parameters are obtained on the basis of the bench erosion test results and scanning electron microscopy data of samples of 20Cr13 steel with a martensitic structure.Research Results. It is suggested to use limiting state diagrams of the ductile and durable materials as their classification criterion. In particular, the initial and critical size of the brittle fracture can be determined on the basis of such a diagram of the hardened materials. These values are used in the basic model to calculate the erosion resistance of the material. Based on theParis equation from the fatigue theory of ParisErdogan, a computational and analytical model for estimating the erosion resistance of the hardened materials is developed and scientifically proven. Their surface degradation occurs according to the mechanism of nucleation and development of cracks of the clasped type. The calculation data are presented for samples of martensitic 20Cr13 steel using the experimentally obtained parameters of theParis equation.Discussion and Conclusions. The results obtained are relevant for the selection, optimization or development of the erosionresistant materials for high-speed blades of the steam-gas turbine and compressor equipment operating under the conditions of condensate formation.